Cognitive research contributions to the development of mathematical hypermedia for geometry learning: Aportes de investigaciones cognitivas a la elaboración de hipermedia para el aprendizaje geométrico - Lugo, Javier (2024)
This paper presents theoretical criteria, based on psycho-cognitive research, to build a hypermedia device oriented to the learning and understanding of Analytic Geometry contents at the university level. The Cognitive Theory of Multimedia Learning (Mayer, 2005, 2009) and its design principles for hypermedia materials are integrated together with specific criteria that have been established to favor understanding in Mathematics (Sierpinska, 1994). In addition, an implementation of the design criteria in a hypermedia device is shown, evidencing how they were incorporated. Finally, a reflection on the production of a hypermedia material for mathematics learning is proposed.